Optimization of enzymatic hydrolysis for the production of antioxidative peptide from Nannochloropsis gaditana using response surface methodology - Md Saleh, Nur Izzati; Wan Ab. Karim Ghani, Wan Azlina; Harun, Mohd Razif; Mustapa Kamal, Siti Mazlina (Universiti Putra Malaysia Press, 2019)
In the present research, microalgae protein hydrolysate of Nannochloropsis gaditana (MPH) was extracted via enzymatic hydrolysis using alcalase enzyme. Hydrolysis conditions like (pH, temperature, enzyme concentration and substrate concentration) were optimized by Response Surface Methodology (RSM) using Central Composite Design (CCD). Four range of independent variables namely; pH (7-9), temperature (45-55°C), substrate concentration (2-6 g/L) and enzyme concentration (0.2-0.4 g/L) were used to study the influence of these parameters on the degree of hydrolysis. The CCD consisted of twenty-four experimental points and six replicates of central points with the optimum conditions obtained from this experiment were at pH 8.14, a temperature 51.4°C, a substrate concentration 5.48 g/L and an enzyme concentration 0.26 g/L with maximum degree hydrolysis of 55.76%. All experiments were fixed at 24 hours reaction time. The degree of hydrolysis of MPH was analysed using O-phthaldehyde (OPA) method to quantify the cleavage of peptide bond. The optimized sample was evaluated for its antioxidant activity using 1,1-Diphenyl-2-picrylhydrazyl (DPPH) assay with 52.19% and 2, 2'- azino-bis (ethylbenzthiazoline-6-sulfonic acid (ABTS) assay with 14.13%. The bioactive peptides contained in Nannochloropsis gaditana have the ability to scavenge free radicals and act as good antioxidants.